Model Penguatan Modal Sosial dalam Kerangka Perluasan Lapangan Kerja bagi Orang Asli Papua di Kabupaten Manokwari - Wanggai, Lodewijk L.; Lumintang, Onnie M.; Fatem, Agustinus; Mambraku, Nomensen St. (JURNAL EKOLOGI BIROKRASI, 2022)
This study aims to reconstruct a model of strengthening social capital to expand opportunities for employment for Papuans, which have been difficult to obtain in Manokwari District. The approach used is grounded theory based on phenomena by applying it in the form of concepts, categories and propositions as a means of construction, reconstruction and elaboration in a social process, with a constructivism paradigm model and emphasizing more on the emic approach. Methods of observation, interviews and documentation. The main instrument is the researcher himself with the help of: a tape recorder notebook, and a camera. The validity of the data was tested using the technique, source, and time triangulation method. Data analysis used descriptive narrative analysis. Research findings show, among others; there is an imbalance of knowledge and understanding of the meaning of belief; there is a tendency for indigenous Papuans to prefer working in the formal sector rather than in the informal sector; the collaboration of social capital and other capital in the process of expanding employment opportunities; indigenous Papuans have no trust in each other, are suspicious of each other, feel inferior; a sense of injustice; the government in empowering no follow-up; the MRPB and LMA should have collaborated with the Otsus faction, Regional Apparatus Organizations (OPD), TNI/Polri, and the private sector; Obstacles to Perda and Perdasus. The strategy to strengthen the structuring of the model within the framework of understanding social relations and the meaning of affirmative action as protection for the basic rights of indigenous Papuans does not yet have a strategy that looks specifically for expanding employment opportunities for indigenous Papuans both in the informal and formal sectors based on local wisdom in the Law -Special Autonomy Act.